2021
DOI: 10.1016/j.ceca.2021.102355
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein emerges as a potent regulator of VDAC-facilitated calcium transport

Abstract: When the Parkinson's disease (PD) related neuronal protein, alpha-synuclein (Syn), is added to the reconstituted mitochondrial voltage-dependent anion channel (VDAC), it reversibly and partially blocks VDAC conductance by its acidic C-terminal tail. Using single-molecule electrophysiology of reconstituted VDAC we now demonstrate that, at CaCl2 concentrations below 150 mM, Syn reverses the channel's selectivity from anionic to cationic. Importantly, we find that the decrease in channel conductance upon its bl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 67 publications
0
39
0
Order By: Relevance
“…The increased levels of cytosolic Ca 2+ in SNc dopaminergic neurons have been further linked to the expression of α-Syn, suggesting a converging pathway for these two pathogenic factors in PD (Lieberman et al, 2017). In support of this, a recent study showed that a-Syn dynamically binds to VDACs and modifies their Ca 2+ permeability (Figure 3; Rosencrans et al, 2021). It is therefore likely that pathological aggregations of α-Syn might affect VDAC binding and thus mitochondrial Ca 2+ buffering.…”
Section: Calcium Handlingmentioning
confidence: 85%
“…The increased levels of cytosolic Ca 2+ in SNc dopaminergic neurons have been further linked to the expression of α-Syn, suggesting a converging pathway for these two pathogenic factors in PD (Lieberman et al, 2017). In support of this, a recent study showed that a-Syn dynamically binds to VDACs and modifies their Ca 2+ permeability (Figure 3; Rosencrans et al, 2021). It is therefore likely that pathological aggregations of α-Syn might affect VDAC binding and thus mitochondrial Ca 2+ buffering.…”
Section: Calcium Handlingmentioning
confidence: 85%
“…Recently, αSyn has been shown to modulate the VDAC permeability to Ca 2+ . In fact, as a result of αSyn binding, VDAC1 selectivity for calcium increases, which leads to a higher Ca 2+ flux through the channel [ 163 ].…”
Section: Vdac As αSyn Binding Partner For Better or For Worsementioning
confidence: 99%
“…Using VDAC reconstitution experiments, it was initially shown by Colombini’s group that VDAC might regulate calcium fluxes to and from mitochondria by voltage gating [ 15 ]. More recently, our group has demonstrated that calcium flux through VDAC is greatly facilitated by αSyn [ 122 ]. These experiments were performed on VDAC reconstituted in a membrane subjected to a CaCl 2 salt gradient that allows measurement of VDACs ionic selectivity in the open and αSyn-blocked states.…”
Section: Physiological Implications Of α-Synuclein and Tubulin Interaction With Vdac: Similarities And Differencesmentioning
confidence: 99%
“…These experiments were performed on VDAC reconstituted in a membrane subjected to a CaCl 2 salt gradient that allows measurement of VDACs ionic selectivity in the open and αSyn-blocked states. From these measurements, the calcium currents through both states were calculated, showing that the calcium permeability of the blocked state is >10 times higher than that of the open state [ 122 ]. The high permeability to calcium in the presence of αSyn is due to the favorable electrostatic environment created by the anionic CTT inside the pore, which overcompensates the physical obstruction of the pore by an order of magnitude.…”
Section: Physiological Implications Of α-Synuclein and Tubulin Interaction With Vdac: Similarities And Differencesmentioning
confidence: 99%